Overflow control for UMTS high-speed downlink packet access. - Lin, P.
This paper proposes overflow control schemes to support high-speed downlink packet access (HSDPA) mechanism in the universal mobile telecommunication system (UMTS). To access the UMTS services, a user equipment (UE) communicates with all cells (base stations) in an active set. However, multiple links between the UE and the cells in the active set may reduce the transmission speed due to interference. Third-Generation Partnership Project specification TR 25.950 proposes HSDPA. In this mechanism, the UE only selects one cell (referred to as the serving cell) in the active set for high-speed downlink transmission. In HSDPA, the radio network controller sends the packet frames to the cells in the active set. For the serving cell, the packet frames are forwarded to the UE. On the other hand, every nonserving cell in the active set queues the packet frames in a buffer. If the link quality between the serving cell and the UE degrades below some threshold, the UE selects the best cell in the active set as the new serving cell. Since the nonserving cells do not send packet frames to the UE, their buffers may overflow. In this paper, we propose schemes to address the buffer overflow issue. Our schemes guarantee that when the buffer of a nonserving cell is full, the previously received packet frames in the buffer can be safely dropped, and after the UE has switched wireless link to the new serving cell, no packet frames are lost.
Keywords: UMTS services; Base stations; Buffer; Frame synchronization; High speed downlink packet access; Interference; Overflow control schemes; Packet frames; Radio network controller; Serving cells; Universal mobile telecommunication system; User equipment